The RNA export factor, Nxt1, is required for tissue specific transcriptional regulation. - Simona Caporilli; Yachuan Yu; Jianqiao Jiang; Helen White-Cooper (PLoS Genetics)
The highly conserved, Nxf/Nxt (TAP/p15) RNA nuclear export pathway is important for export of most mRNAs from the nucleus, by interacting with mRNAs and promoting their passage through nuclear pores. Nxt1 is essential for viability; using a partial loss of function allele, we reveal a role for this gene in tissue specific transcription. We show that many Drosophila melanogaster testis-specific mRNAs require Nxt1 for their accumulation. The transcripts that require Nxt1 also depend on a testis-specific transcription complex, tMAC. We show that loss of Nxt1 leads to reduced transcription of tMAC targets. A reporter transcript from a tMAC-dependent promoter is under-expressed in Nxt1 mutants, however the same transcript accumulates in mutants if driven by a tMAC-independent promoter. Thus, in Drosophila primary spermatocytes, the transcription factor used to activate expression of a transcript, rather than the RNA sequence itself or the core transcription machinery, determines whether this expression requires Nxt1. We additionally find that transcripts from intron-less genes are more sensitive to loss of Nxt1 function than those from intron-containing genes and propose a mechanism in which transcript processing feeds back to increase activity of a tissue specific transcription complex.